Environmental Safety and Legal Regulation of Medical Waste Management: International Experience - SEILKASSYMOVA, Roza; NURMUKHANKYZY, Daniya; RZABAY, Aktoty; BAKTYKHOZHAYE, Zhangali; NESSIPBAYEVA, Indira (Journal of Environmental Management and Tourism, 2022)
The article deals with the issues of protecting the population and the environment from the harmful effects of medical waste. Medical waste is dangerous, as the biomaterial carrying the virus accumulates. The list of medicines used in the activities of medical institutions, along with the risk of waste, is also extensive. In the world practice, the issues of neutralization and processing of medical waste are considered. In addition, the analysis of sanitary requirements and legal regulations for the disposal of medical waste was carried out. The hazard class of medical waste is considered depending on the degree of their epidemiological, toxicological and radiation hazard, as well as negative impact on the habitat .